La responsabilidad del empleador por accidentes de trabajo y enfermedades ocupacionales: retrospectiva y futuro - Puntriano Rosas, César (Universidad ESAN, 2021)
The recent trend in labor jurisprudence passes liability to the employer in the event of an accident at work or occupational disease. This violates the theory of contractual civil liability, applicable to the employment relationship, which requires fraud, gross negligence or at least slight negligence for the generation of the employer’s duty to compensate the employee. In this paper we legally analyze how employer responsibility has evolved and critically approach the current criteria, formulating some proposals for future change.

La reciente tendencia de la jurisprudencia laboral pasa por responsabilizar al empleador ante un accidente de trabajo o una enfermedad profesional. Ello infringe la teoría de la responsabilidad civil contractual, aplicable a la relación jurídica laboral, la cual exige dolo, culpa grave o, al menos, culpa leve para la generación del deber de indemnizar a cargo del empleador. En este trabajo se analiza jurídicamente cómo ha evolucionado la responsabilidad del empleador y se aborda críticamente el criterio vigente formulando algunas propuestas de cambio.
Keywords: Public liability; Safety and health at work; Responsabilidad civil; Employer´s legal obligations for worker’s compensation; Seguridad y salud en el trabajo; Obligación de compensar al trabajador; Case law; Pleno jurisdiccional; https://purl.org/pe-repo/ocde/ford#5.05.01